Apocrine Carcinoma of Breast: A Case Report with Review of the Literature - Jyotsna V. Wader; Akash Jain; Suresh J. Bhosale; Pandurang G. Chougale; Sujata S. Kumbhar (Hindawi Limited, 2013)
Apocrine carcinoma is a very rare form of breast malignancy with an incidence of <1% of female invasive breast carcinoma. We report a case of apocrine carcinoma in a 42-year female with marked adenosis showing apocrine metaplasia and discuss the criteria to diagnose apocrine carcinoma with the emerging concept of androgen receptor positivity with its implication on treatment and management of the patient.